Toward Identifying APT Malware through API System Calls. (9th December 2021) - Wei, Chaoxian; Li, Qiang; Guo, Dong; Meng, Xiangyu
Abstract : Self-developed malware was usually used by advanced persistent threat (APT) attackers to launch APT attacks. Therefore, we can enhance the understanding and cognition of APT attacks by comprehending the behavior of APT malware. Unfortunately, the current research cannot effectively explain the relationship between the recognition, detection, and defense of APT. The model of similar studies also lacks an explanation about it. To defend against APT attacks and inquire about the similarity of different APT attacks, this study proposes an APT malware classification method based on a combination of multiple deep learning algorithms and transfer learning by collecting malware used in several famous APT groups in public. By extracting the application programming interface (API) system calls, with the vector representation of features by combining dynamic LSTM and attention algorithm, we can obtain API at different APT families classification contributions trained dynamic. Thus, we used transfer learning to perform multiple classifications of the APT family. This study aims to reduce the burden of network security staff from reviewing a large number of suspicious files when defending against APT attacks. Additionally, it can effectively intercept them in the initial invasion stage of APT to perform targeted defense against specific APT attacks by combining threat intelligence in public. The experimental result shows that the proposed method can achieve 99.2% in distinguishing common malware from APT malware and assign APT malware to different APT families with an accuracy of 95.5%.